2017
DOI: 10.5455/aim.2017.25.178-181
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Obstructive Hydronephrosis with Color Doppler Ultrasound

Abstract: Background:The obstructive hydronephrosis is a term that implicates the structural and functional changes of the kidneys as a result of difficulties in the flow of urine. Hydronephrosis specifically describes dilation and swelling of the kidney. Hydronephrosis is a condition that typically occurs when the kidney swells due to the failure of normal drainage of urine from the kidney to the bladder. Our aim was to evaluate the degree of hydronephrosis, causes and diagnostic method. Material andMethods:This is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 9 publications
5
14
0
1
Order By: Relevance
“…Distribution of the grades of hydronephrosis in this study is similar to a previous survey of Nuraj P et al (2017), who reported that the grades of hydronephrosis were as follows: 48%grade 2, 22.8% grade 1, 16.2% grade 3 and 12.5% grade 4. 10 In this study, there are significant associations between the stone length and location with the grade of hydronephrosis whereas the patient’s gender has no relationship with the grade. These results are consistent with a previous study by Song Y et al (2015) regarding the stone length and patient’s gender but not compatible with him regarding the stone location.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Distribution of the grades of hydronephrosis in this study is similar to a previous survey of Nuraj P et al (2017), who reported that the grades of hydronephrosis were as follows: 48%grade 2, 22.8% grade 1, 16.2% grade 3 and 12.5% grade 4. 10 In this study, there are significant associations between the stone length and location with the grade of hydronephrosis whereas the patient’s gender has no relationship with the grade. These results are consistent with a previous study by Song Y et al (2015) regarding the stone length and patient’s gender but not compatible with him regarding the stone location.…”
Section: Discussionmentioning
confidence: 57%
“…This result is compatible with previous studies by Hall (2009) and Nuraj P et al (2017), who reported that renal calculi in males were nearly twice as it was in females. 9 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…Nuraj P et al studied 136 cases and found that majority were males. 7 Authors also found that males were more than females. The mean age of the males was also more than females.…”
Section: Discussionmentioning
confidence: 96%
“…The authors praised the utility of USG. 7 Orabi M et al studied 105 cases of hydronephrosis and found that the majority were males. 8 Authors also found that males were more than females.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the advancement of inspection technology, magnetic resonance imaging (MRI) can not only provide more morphological information than ultrasound, but also computer-assisted post-processing technology can objectively quantify its functional assessment and classify obstruction like DRS [1]. At present, there is still a certain deficiency in the quantitative analysis of renal function by MR urography (MRU).…”
Section: Introductionmentioning
confidence: 99%